Russian history in the Belarusian State University: transformation of institutionality, teaching practices and research (1921–2024) - Yanouski, Aleh A. (Journal of the Belarusian State University. History, 2024)
Based on a wide range of sources, the stages of institutionalisation of Russian history as a science, directions, forms and methods of its teaching at the Belarusian State University from the beginning of activity of the institution to the 90th anniversary of the foundation of the faculty of history in its structure (2024), are considered. Conclusions are made not only about the undoubted influence of the political component of each stage on these processes, the desire of teachers and students of all generations to improve the efficiency of their work and study, but also about the objective requirements of the time, questions of the civilisational purpose of the university and the internal logic of its multi-vector development.
Keywords: Belarusian State University; Russian studies; department of Russian history; higher education of Belarus